Ethanol is indispensable for virucidal hand antisepsis and without toxic risks in daily use - Kramer, Axel; Benkhai, Hicham; Jäkel, Christian; Zwicker, Paula (GMS Hygiene and Infection Control, 2023)
The approval of ethanol by the Biocidal Products Regulation has been under evaluation since 2007 due to controversial opinions on the risk assessment. Because of this critical situation, 2022 a memorandum was published to verify whether the use of ethanol for hand antisepsis poses any hazard. On the basis of the memorandum a toxicological evaluation of ethanol-based hand rubs is given.